1996
DOI: 10.1046/j.1365-2168.1996.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischaemia-reperfusion injury

Abstract: Ischaemia-reperfusion injury is a complex interrelated sequence of events that classically involves the vascular endothelium and activated leucocytes. During the ischaemic phase the endothelium is primed both to produce free radicals and to secrete chemoattractants. The resultant neutrophil sequestration serves to amplify the injury, but damage is not confined to the postischaemic area and more generalized effects typically follow. The situation in the kidney is complex for, while ischaemia primes the tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 118 publications
1
91
0
2
Order By: Relevance
“…However, the kidney may behave somewhat differently in ischemia-reperfusion injury. While neutrophils are recognized to play a significant role in ischemia-reperfusion injury in many different extrarenal organs, their role in the kidney is still debated or even negated [4, 36, 37]. Not unexpectedly, monocytes/macrophages do not seem to play a crucial role in our model.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the kidney may behave somewhat differently in ischemia-reperfusion injury. While neutrophils are recognized to play a significant role in ischemia-reperfusion injury in many different extrarenal organs, their role in the kidney is still debated or even negated [4, 36, 37]. Not unexpectedly, monocytes/macrophages do not seem to play a crucial role in our model.…”
Section: Discussionmentioning
confidence: 70%
“…Subsequent organ reperfusion may further aggravate ischemic cell damage [2]. Reperfusion with oxygenated blood is accompanied by synthesis and release of reactive oxygen species (ROS) and other inflammatory mediators by leukocytes and parenchymal cells such as endothelium [2, 3, 4, 5]. Cytotoxic ROS play a key role in the pathogenesis of ischemia-reperfusion injury causing adverse effects like lipid peroxidation and mitochondrial damage [1, 2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…35 Indeed, clinical and experimental studies have shown that I/R injury is mediated by ROS. [36][37][38] It has been demonstrated that ROS-mediated cellular damage occurs when oxygen is supplied to the tissue by reperfusion and tissue detoxification capacity is deficient for ROS formation. 39 Hence, oxidation of cell protein and membrane lipid peroxidation causes cell death and damage of DNA helix.…”
Section: Discussionmentioning
confidence: 99%
“…Renal ischemia, whether caused by shock or during surgery or transplantation, is a major cause of ARF, initiating a complex and interrelated sequence of events resulting in injury to and eventual death of renal cells [2]. The prognosis is complicated by the fact that reperfusion, although essential for the survival of ischemic renal tissue, causes additional damage (reperfusion injury) [3]which contributes to the renal dysfunction and injury associated with ischemia/reperfusion (I/R) of the kidney.…”
Section: Introductionmentioning
confidence: 99%